Strategi Manajemen Media dalam Menjaga Aktualitas Berita di Media Online (Studi Kasus Pemberitaan Banjir Jakarta 2014 di Okezone.com) - M.Budi Santosa (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
The problem in this research is about how online media management strategy and modern management style to be able to keep actuality preaching. Case in point is the news in Okezone.com about flooding in Jakarta in 2014. The purpose of this study to determine the online media management strategy Okezone.com applying management principles (modern) so as to meet the challenges that the actual generated news and fulfill the function of the mass media, as well as to know the function of management related to the application of management principles (modern). Theories and concepts presented in this study, in addition to using the theory of mass communication that refers to McLuhan thought, also uses the concept of mass media management, the concept of the mechanism of news production, and modern management concept that is reflected from the implementation of the POAC (Planning, Organizing, Actuating, and controlling). Constructivist research paradigm. The results found Okezone.com, try different strategies to present actuality of news production news. Okezone.com also implement a modern management system, despite facing many obstacles, such as: human resources, inadequate equipment, and the importance of support from the board of directors. Keywords: mass media management, modern management, production news, current events, speed